TEACHERS’ PERCEPTIONS OF THE IMPLEMENTATION OF THE DEEP LEARNING APPROACH IN ISLAMIC RELIGIOUS EDUCATION AND CHARACTER EDUCATION COURSES AT PALEMBANG STATE HIGH SCHOOL 1 - Muhamad Yudistira Nugraha; Ahmad Zainuri; Muhamad Fauzi (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze teachers' perceptions of the concepts and principles of the deep learning approach, their understanding and experience in implementing it through the use of digital technology, as well as the obstacles and solutions in Islamic Religious Education and Character (PAIBP) learning at SMA Negeri 1 Palembang. The method used is qualitative with a case study approach. Research subjects were selected purposively, namely PAIBP teachers. Data were collected through non-participant observation, in-depth interviews, and documentation of learning tools and school policies. Data analysis was carried out through reduction, presentation, and conclusion drawing, with validity testing through source and technique triangulation. The results show that teachers have positive perceptions of deep learning as an approach that emphasizes deep understanding, reflection, and internalization of values, although the depth of understanding varies among teachers. Implementation was carried out systematically through problem-based planning, reflective discussions, projects, and authentic assessment. AI was utilized for religious case analysis and enriching students' perspectives; Kahoot and Gimkit were used as interactive formative evaluation tools; while audiovisual media presented real learning contexts. Technology integration supports meaningful, mindful, and joyful learning. The impact is evident in the increased student engagement, critical thinking, and religious awareness. Obstacles include digital literacy limitations, limited training, and cognitive evaluation orientation, which are addressed through strengthening MGMP forums, authentic assessment, technology-based reflection, and continuous training.